Cases of difficult-to-access benign tumors with the potential risk for bone fracture - Luben Stokov; Ivelin Kostadinov; Georgi Georgiev; Kristian Nastev; Luben Lubenov Stokov; Alexandar Kostadinov (Journal of the Bulgarian Orthopaedics and Trauma Association)
During the period from 2022-2023, three patients underwent surgical treatment involving curettage and bone grafting at our clinic (2 females and 1 male) due to hip pain. In two of them, a non-ossifying fibroma of the femoral neck and acetabulum was observed, while in the third patient, a bone cyst in the femoral neck was established. Due to possible fractures in these areas, the patients underwent surgery involving curettage and bone grafting with a synthetic bone substitute. Postoperatively, the patients had no pain and full range of motion.